Splenic artery embolization: An alternative approach in a critically ill patient with autoimmune hemolytic anemia - Mine Durusu Tanrıöver; Bora Peynircioğlu; Begüm Ergan Arsava; Arzu Topeli İskit (Turkish Journal of Hematology, 2011)
Assessment of general health status and hematological parameters usually precedes the use of invasive diagnostic and therapeutic procedures in critically ill patients. Angiography can be effective and safe as a substitute for major surgical procedures, or as a bridging therapy in such cases. We present a critically ill patient with hemolytic anemia that underwent splenic artery embolization as a bridging therapy. We aimed to emphasize that minimally invasive approaches and multidisciplinary care can be utilized in the treatment of critically ill patients with accompanying hematological disease.